2009
DOI: 10.1007/s11295-009-0206-0
|View full text |Cite
|
Sign up to set email alerts
|

Highly efficient transformation of the GFP and MAC12.2 genes into precocious trifoliate orange (Poncirus trifoliata [L.] Raf), a potential model genotype for functional genomics studies in Citrus

Abstract: Precocious trifoliate orange (Poncirus trifoliata [L.] Raf), an extremely early flowering mutant of P. trifoliata, is an attractive model for functional genomics research in Citrus. A procedure for efficient regeneration and transformation of this genotype was developed by using green fluorescent protein (GFP) gene as visual marker and etiolated stem segments as explants. In vivo monitoring of GFP expression permitted a rapid and easy discrimination of transgenic shoots and escapes. Transformation efficiency w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…Compared with other Citrus species, this transformation efficiency was higher than that of grapefruit (3.6%) (Yang et al 2000), equivalent to that of Mexican lime (3.5-4.6%) (Peña et al 1997, Domínguez et al 2000, and was lower than that of sweet orange (7.6-15.0%) and precocious trifoliate orange (20.7%) (Peña et al 1995, Mendes et al 2002Tan et al 2009). In kumquat transformation, one possible obstacle leading to low transformation efficiency, is the high frequent regeneration of escapes, and another potential obstacle was the high frequency of chimeras as revealed by GUS analyses.…”
Section: Factors Influencing Transformation Efficiency Of 'Meiwa' Kummentioning
confidence: 66%
See 2 more Smart Citations
“…Compared with other Citrus species, this transformation efficiency was higher than that of grapefruit (3.6%) (Yang et al 2000), equivalent to that of Mexican lime (3.5-4.6%) (Peña et al 1997, Domínguez et al 2000, and was lower than that of sweet orange (7.6-15.0%) and precocious trifoliate orange (20.7%) (Peña et al 1995, Mendes et al 2002Tan et al 2009). In kumquat transformation, one possible obstacle leading to low transformation efficiency, is the high frequent regeneration of escapes, and another potential obstacle was the high frequency of chimeras as revealed by GUS analyses.…”
Section: Factors Influencing Transformation Efficiency Of 'Meiwa' Kummentioning
confidence: 66%
“…In our study, that an elevated concentration (100 mg/l) of Km during development of resistant kumquat shoots effectively inhibited the elongation of non-transformed shoots was also observed. Herein, it was suggested that genotype rather than other factors accounted for low efficiency since much higher transformation efficiency was achieved with another citrus genotypes like precocious trifoliate orange, under the same transformation and regeneration conditions (Tan et al 2009). In transformation of 'Meiwa' kumquat, seedling age of explants significantly affected transformation efficiency.…”
Section: Factors Influencing Transformation Efficiency Of 'Meiwa' Kummentioning
confidence: 99%
See 1 more Smart Citation
“…One of the advantages of using reporter marker genes, like Escherichia coli uidA or Aequorea victoria gfp gene, is to discriminate transgenic events by positive reporter expression in recovery lines (Saika and Toki 2009;Tan et al 2009). Herein, we report a visual selection system for transformed cells using a GFP marker after Agrobacteriummediated transformation in citrus.…”
Section: Discussionmentioning
confidence: 99%
“…Four replicates of each reaction were performed. Output data generated by the instrument onboard software Sequence Detector Version1.3.1 (PE Applied Biosystems) were transferred to a custom designed Microsoft Excel macro for analysis (Tan et al 2009). …”
Section: Real-time Rt-pcr Quantificationmentioning
confidence: 99%